Role of Renewable Energy Sources in the World - Mammadov N.S.; Ganiyeva N.A.; Aliyeva G.A. (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2022)
The severe climate crisis on the planet has led to the need to quickly abandon fossil fuels and switch to alternative energy,